Quantifying the impacts of defaunation on natural forest regeneration in a global meta-analysis - Charlie J. Gardner (Nature Portfolio, 2019)
The defaunation of vertebrates may disrupt forest functioning through the loss of plant-animal interactions, but impacts on forests remain unquantified. Here the authors show that seed dispersal is a key interaction and defaunation of primates and birds negatively impacts forest regeneration.